Haemosporidian parasites of Canada Warblers ( Cardellina canadensis ) and Black-throated Blue Warblers ( Setophaga caerulescens ): prevalence, diversity, and associations with physiological condition during migration - Gabriella L Orfanides; Susan S. Pagano (Avian Conservation and Ecology)
Avian malaria ( Plasmodium spp.) and related haemosporidian parasites ( Leucocytozoon spp. and Haemoproteus spp.) are widespread in birds, yet studies investigating prevalence and diversity of haemosporidians are lacking for many Nearctic-Neotropical migrants. Furthermore, the impact that infections may have on the condition or behavior of birds during migration is still poorly understood. Here, we used nested PCR and DNA sequencing to determine parasite prevalence and identify genetic lineages of haemosporidians in Canada Warblers ( Cardellina canadensis ) and Black-throated Blue Warblers ( Setophaga caerulescens ) during their migration stopover on the south shore of Lake Ontario. We further evaluated if haemosporidian infections were related to immune condition, as assessed via total white blood cell (WBC) counts and heterophil/lymphocyte (H/L) ratios, or refueling patterns and/or migration timing. We found a haemosporidian prevalence of 51.5% in 66 birds; however, there was a greater haemosporidian prevalence in Black-throated Blue Warblers relative to Canada Warblers. We detected 15 cytochrome b lineages of parasites, including 4 novel lineages. In Black-throated Blue Warblers, infected birds had significantly higher total WBC counts compared to uninfected birds. Across species, females had lower H/L ratios when infected, whereas the opposite trend was observed in males. Plasma metabolites (triglyceride, β-hydroxybutyrate, uric acid) were not associated with infection status, and infection was not related to arrival date at the spring stopover site. Results provide insight into the diversity of haemosporidians that infect two species of migratory warblers and illustrate that blood parasite infections are a routine challenge that these birds face during migration. Although haemosporidian infections may be associated with a heightened immune response in some scenarios, the findings of this correlative study provide no evidence that Canada Warblers and Black-throated Blue Warblers experience physiological or behavioral trade-offs as a result of infections.